2022
DOI: 10.1002/eat.23830
|View full text |Cite
|
Sign up to set email alerts
|

Toward inclusivity: A systematic review of the conceptualization of sexual minority status and associated eating disorder outcomes across two decades

Abstract: Objective Sexual minority (SM) groups (e.g., those who identify as lesbian, gay, bisexual, questioning, queer, asexual, or those who feel their sexual orientation identity cannot be captured with existing terminology [LGBQA+] and those who report same‐sex or same‐gender attraction and/or behavior) are at elevated risk for eating disorder (ED) symptoms and behaviors. However, the ways in which this risk varies across SM is less clear, and findings are not fully convergent. Evolution in the definition and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…There is some evidence to suggest a potential link between the use of some products and a later eating disorder diagnosis. However, this appears to be more of a symptom or associated behavior potentially valuable as a screening tool as opposed to demonstrating causality [11]. Therefore, it may be reasonable to state that the abuse, not use, of certain supplements may be associated with an eating disorder rather than being a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence to suggest a potential link between the use of some products and a later eating disorder diagnosis. However, this appears to be more of a symptom or associated behavior potentially valuable as a screening tool as opposed to demonstrating causality [11]. Therefore, it may be reasonable to state that the abuse, not use, of certain supplements may be associated with an eating disorder rather than being a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…A risk factor occurs before the associated outcome; it is a characteristic associated with an increased likelihood of the outcome being studied. It can be used to determine highrisk and low-risk subgroups [11]. It should not be confused with symptoms or behaviors associated with the disease itself.…”
Section: Known Risk Factors For Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the research attracted a number of university educated students who were studying gender—a pursuit which may be more associated with marginalized communities in the Chinese context. Western studies have explored how occupying a sexual minority identity may increase the risk for EDs (although the results are uneven and there is more work on males) [ 51 ], and how experiences of sexual marginalization can shape the political and personal meanings of eating/body distress [ 36 ]. Nevertheless, the participants in the study who identified as pan/bi/lesbian did not refer to issues of sexuality in interview, whether explicitly or implicitly.…”
Section: Methodsmentioning
confidence: 99%
“…People that are part of Sexual and Gender Minorities (SGMs) seem to be particularly at risk—that is, people who have either a sexual orientation other than heterosexual (e.g., gay, lesbian, bisexual, pansexual 1 ) or a gender identity that is not consistent with one’s assigned gender at birth (e.g., trans, non-binary, gender non-conforming). The prevalence of disordered eating has been found to be higher in SGMs when compared to heterosexual or cisgender people [ 6 9 ]. SGMs have also been found to be at significant risk for body image concerns, such as increased body dissatisfaction [ 10 , 11 ], weight bias [ 12 ] and weight dissatisfaction [ 13 , 14 ], which are closely linked to disordered eating.…”
Section: Introductionmentioning
confidence: 99%